Left ventricular diastolic function in CMR using transmitral velocity in Thalassemia patients: correlations with echocardiography - Mohd Zaki, Husna; Abu Hassan, Hasyma; Abdul Aziz, Yang Faridah; Mohammed, Yusri (Iranian Heart Association, 2022)
Objectives: We sought to compare diastolic values in cardiac magnetic resonance imaging (CMR) compared with echocardiography in assessing left ventricular diastolic function in patients with thalassemia. Background: Left ventricular assessment by CMR is mainly limited to the evaluation of the systolic function of the heart and is widely used in clinical practice. On the other hand, the gold standard for diastolic function assessment is echocardiography. The role of CMR in diastolic function assessment is less well-established clinically, despite the importance of the early diagnosis of diastolic dysfunction, which precedes systolic dysfunction. Methods: Forty-five subjects (mean age =27.8±10.9 y) who underwent CMR and echocardiography on the same day were evaluated. Diastolic function parameters using the technique of the transmitral flow (the E wave, the A wave, the E/A ratio, and the deceleration time) of the left ventricle were evaluated via both CMR and echocardiography. Results: The E/A ratio of the transmitral flow to assess diastolic parameters in CMR correlated well with echocardiography (r=0.745*, P<0.001), while the E and A values had weak correlations between the 2 modalities (r=0.301, P<0.05 and r=0.343, P<0.05). The measurement of the deceleration time in CMR had no statistically significant correlation with that of echocardiography (r=0.219, P=0.152). A weak correlation existed between the diastolic index measured using the technique of the fractional area change of the left ventricle and the E/A ratio measured in echocardiography (r=0.325, P[removed]